2018
DOI: 10.1002/pc.24885
|View full text |Cite
|
Sign up to set email alerts
|

The reinforcing mechanism of mechanical properties of bamboo fiber bundle‐reinforced composites

Abstract: In this study, bamboo fiber bundle‐reinforced composites (BFCs) were prepared from Neosinocalamus affinis and phenol‐formaldehyde resins. The strength and modulus of BFC were more than double those of the raw bamboo. By using micro computed tomography, scanning electron microscopy and nanoindentation tests, the reinforcement mechanism of the bamboo‐based composites was investigated. And the details were summarized as follows. As the strongest parts of bamboo, the mechanical properties of the fiber cells were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…A positive linear relationship was found between density and MOR (or MOE) no matter whether the measurements were done parallel or perpendicular to the fiber direction of bamboo scrimber [48]. As the density increased from 1.02 to 1.3 g/cm 3 , the MOR of bamboo scrimber almost increased by 50%, from 271 to 398 MPa and the MOE increased from 26.4 to 32.3 GPa [21]. The water absorption decreased from 43.0 to 5.01% as the density increased from 0.8 to 1.2 g/cm 3 [35], which could be attributed to the closeness of bamboo lumens such as vessels, parenchymas and fibers caused by highpressure hot-pressing process.…”
Section: Densitymentioning
confidence: 89%
See 2 more Smart Citations
“…A positive linear relationship was found between density and MOR (or MOE) no matter whether the measurements were done parallel or perpendicular to the fiber direction of bamboo scrimber [48]. As the density increased from 1.02 to 1.3 g/cm 3 , the MOR of bamboo scrimber almost increased by 50%, from 271 to 398 MPa and the MOE increased from 26.4 to 32.3 GPa [21]. The water absorption decreased from 43.0 to 5.01% as the density increased from 0.8 to 1.2 g/cm 3 [35], which could be attributed to the closeness of bamboo lumens such as vessels, parenchymas and fibers caused by highpressure hot-pressing process.…”
Section: Densitymentioning
confidence: 89%
“…The bamboo outer skin and inner skin were usually removed via planing process or splitting process, and the utilization rate of bamboo was about 50-60%. After more than 10 years' efforts, the Research Institute of wood industry in Chinese Academy of Forestry developed a new generation of bamboo scrimber (also called bamboo-based fiber composite) by using small-diameter scattered bamboo as raw material [6,7,[19][20][21]. Long bamboo fiber bundles are extracted directly from bamboo culm using the novel mechanical method without removing the bamboo outer skin and inner skin.…”
Section: Evolution Of Bamboo Scrimbermentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the parenchyma, vessels, and fibers of bamboo were compacted to different degrees, and the cell walls were folded or even crushed [22,[45][46][47][48]. Phenolic resin was redistributed and cured under hygrothermal condition with high pressure, forming the macrobonding interface between the resin and the substrate surface, the microscale interface between the resin and the vessel as well as the cell cavity of parenchyma cells, and the nanoscale interface between the resin and the cell wall of parenchyma cells [49]. In terms of chemical composition, hemicellulose in the cell wall was degraded, soluble extracts were further decomposed, and the relative crystallinity of cellulose was decreased [15,50].…”
Section: Research Progress Of Bamboo Recombinationmentioning
confidence: 99%
“…Driven by sustainability and material performance, bamboo fiber composites (BFCs) can be produced as high-strength, dimensionally stable and durable products [ 3 , 4 ], reducing the pressing need for tropical hardwoods and structural lumbers. Versatile BFC products are used in wind turbine blades, building panels and columns, landscape architecture, highway fences, shipping container flooring, interior/exterior flooring and decking and furniture [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%